Episodic air pollution is associated with increased DNA fragmentation in human sperm without other changes in semen quality - Rubes, Jiri; Selevan, Sherry G; Evenson, Donald P; Zudova, Dagmar; Vozdova, Miluse; Zudova, Zdena; Robbins, Wendie A; Perreault, Sally D (Human reproduction (Oxford, England), 2005)
BACKGROUND: This study examined potential associations between exposure to episodes of air pollution and alterations in semen quality. The air pollution, resulting from combustion of coal for industry and home heating in the Teplice district of the Czech Republic, was much higher during the winter than at other times of year with peaks exceeding US air quality standards. METHODS: Young men from Teplice were sampled up to seven times over 2 years allowing evaluation of semen quality after periods of exposure to both low and high air pollution. Routine semen analysis (sperm concentration, motility and morphology) and tests for sperm aneuploidy and chromatin integrity were performed, comparing measurements within each subject. Exposure was classified as high or low based on data from ambient air pollution monitoring. RESULTS: Using repeated measures analysis, a significant association was found between exposure to periods of high air pollution (at or above the upper limit of US air quality standards) and the percentage of sperm with DNA fragmentation according to sperm chromatin structure assay (SCSA). Other semen measures were not associated with air pollution. CONCLUSION: Exposure to intermittent air pollution may result in sperm DNA damage and thereby increase the rates of male-mediated infertility, miscarriage, and other adverse reproductive outcomes.
Keywords: dospělí; Tobacco Smoke Pollution; znečištění tabákovým kouřem; průzkumy a dotazníky; Models, Statistical; biologické markery; aneuploidie; spermie; Biomarkers; Adult; DNA Fragmentation; Semen; fragmentace DNA; Surveys and Questionnaires; Chromatin; Spermatozoa; Metals; Abortion, Spontaneous; Time Factors; časové faktory; znečištění ovzduší; DNA; lidé; Air Pollution; statistické modely; kovy; sperma; Sperm Count; kohortové studie; Infertility, Male; Cohort Studies; Male; Air Pollutants; chromatin; samovolný potrat; vystavení vlivu životního prostředí; mužská infertilita; mužské pohlaví; Aneuploidy; látky znečišťující vzduch; počet spermií; Environmental Exposure; Humans